La Inclusión Educativa en la Universidad Politécnica Salesiana : estudio de caso de un estudiante con discapacidad intelectual periodos académicos 49-50 - García Chérrez, Jessica Belén (2018)
The present study is conceived as a descriptive research, with a field design, broad documentary support and under a qualitative approach, focused on a case study where the analysis of the inclusion of students with intellectual disabilities in the Salesian Polytechnic University is considered, within the framework of a student who is with intellectual disability. The methodology used consisted in data collection, through direct participant observation, interviews with the family group, teachers, educational units, and classmates, thus elaborating a content portfolio with all the information gathered about it. Also the bibliographic review of authoritative sources and broad academic rigor, as well as the consultation of experts in the area under study and research methodology. The main findings are presented chronologically in the different stages of the educational cycle of the student under study and are aimed at recognizing the academic, therapeutic, family and institutional efforts to reach the competences in each of the training cycles addressed by the student, likewise the difficulties observed that in no aspect constituted an impediment to the achievement of academic objectives. It is concluded that in all stages of the academic life of the student object of the present study, the unlimited support of the educational system is demonstrated in the implementation of comprehensive strategies for the achievement of its objectives within the framework of respect for its best interests.